Preparation method and application of migration-resistant composite anti-aging agent
By esterification reaction of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 2,4-dihydroxybenzophenone, a migration-resistant composite anti-aging agent was prepared, which solved the existing anti-oxygen The problem of single function and narrow application range of agents and ultraviolet absorbers has achieved significant improvement in the anti-aging performance of high-density polyethylene.
Patent Information
- Application Number
- CN202411555485.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing antioxidants and ultraviolet absorbers have single functions, narrow application range, and easy to migrate, making it difficult to effectively improve the aging resistance of high-density polyethylene.
Through the esterification reaction, 3,5-ditert-butyl-4-hydroxyphenylpropionic acid is combined with 2,4-dihydroxybenzophenone to prepare a migration-resistant composite anti-aging agent, which can absorb UV and other compounds. Light reduces molecular chain reactions and captures free radicals to terminate chain reactions.
This composite anti-aging agent is not easy to migrate, has good compatibility and stability, significantly improves the anti-aging performance of high-density polyethylene and has a wider range of applications.
Smart Images

Figure CN119431148A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material anti-aging, and in particular to a migration-resistant composite anti-aging agent and a preparation method and application thereof. Background Art
[0002] High-density polyethylene (HDPE) is a highly crystalline, non-polar thermoplastic resin with good wear resistance, electrical insulation, toughness and cold resistance; it has good chemical stability, is insoluble in any organic solvent at room temperature, is resistant to corrosion by acids, alkalis and various salts, and has low water absorption; however, high-density polyethylene has poor aging resistance and environmental stress cracking resistance, especially thermal oxidation will greatly reduce its performance, so antioxidants and ultraviolet absorbers must be added to the resin to improve this deficiency.
[0003] Plastic aging is usually caused by radiation, high temperature and contact with oxygen, which lead to the generation of active free radicals in the molecular chain, thus triggering a series of chain reactions and reducing the molecular weight. Therefore, the methods of anti-oxidation reaction can be divided into three types: capturing free radicals generated by photoaging, decomposing hydroperoxides generated by photoaging, and anti-oxidation synergy, such as absorbing ultraviolet light, to reduce the source of molecular chain reactions. However, the antioxidants and ultraviolet absorbers commonly used in the market have a narrow scope of application and a single function.
[0004] Hindered phenol antioxidants are one of the most widely used phenolic antioxidants. Among them, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid is a common basic raw material for the synthesis of hindered phenolic antioxidants. It is an excellent hydrogen donor and works by donating phenolic hydrogen to free radicals generated by molecular chains. The generated phenoxy free radicals are resonance-stabilized and have the ability to further capture other free radicals, thereby destroying the chain reaction produced by free radical oxidation during polymer aging.
[0005] Benzophenone ultraviolet absorbers have excellent ultraviolet absorption performance and wide applicability to materials. They can form internal hydrogen bonds in their molecules to form a chelate ring. After absorbing ultraviolet light energy, the ring undergoes molecular thermal vibration, and the internal hydrogen bonds are destroyed to open the ring. The energy of ultraviolet light is converted into heat and released. The strength of the hydrogen bonds in the molecule is closely related to the photostability. The stronger the hydrogen bonds, the higher the stability. At the same time, the electronegativity of the substituents on the benzene ring also affects its ultraviolet absorption ability. 2,4-dihydroxybenzophenone is a more commonly used structure in benzophenone ultraviolet absorbers, but due to its simple structure and small molecular weight, its ultraviolet absorption effect is poor and it is easy to migrate during processing and use.
[0006] The invention conducts esterification reaction on 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 2,4-dihydroxybenzophenone. The synthesized compound can absorb ultraviolet light to reduce the source of molecular chain reaction and capture free radicals generated by photoaging to terminate the chain reaction. Meanwhile, the molecular weight is moderate to achieve the composite anti-aging effect. Summary of the invention
[0007] The present invention aims at the shortcomings of the prior art that antioxidants and ultraviolet absorbers have single functions, unclear effects, narrow application ranges, and are easy to migrate out of the material surface. A preparation method and application of a migration-resistant composite anti-aging agent are provided to solve the problems existing in the prior art.
[0008] The first object of the present invention is to provide a migration-resistant composite antioxidant.
[0009] The second object of the present invention is to provide a method for preparing a migration-resistant composite anti-aging agent.
[0010] In order to achieve the above-mentioned first object, the present invention adopts the following technical scheme:
[0011] A migration-resistant composite anti-aging agent having a structure as shown in formula (1):
[0012]
[0013] The molecular formula of the migration-resistant composite anti-aging agent is C 30 H 34 O5.
[0014] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0015] A method for preparing a migration-resistant composite anti-aging agent, the synthetic process route is:
[0016]
[0017] The preparation method thereof comprises the following steps:
[0018] 1) In the presence of catalyst 1, 3,5-di-tert-butyl-4-hydroxybenzenepropionic acid is reacted with thionyl chloride to obtain a 3,5-di-tert-butyl-4-hydroxybenzenepropanoyl chloride intermediate represented by formula (2).
[0019]
[0020] 2) In the presence of catalyst 2, the intermediate compound represented by formula (2) is subjected to an esterification reaction with 2,4-dihydroxybenzophenone to obtain a hindered phenol antioxidant combined with an ultraviolet absorber represented by formula (1), i.e., a migration-resistant composite antioxidant.
[0021] Furthermore, in step 1), the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to thionyl chloride is 1 to 1.2:1.
[0022] Furthermore, in step 1), catalyst 1 is any one of N,N-dimethylformamide, 4-dimethylaminopyridine and triethylamine.
[0023] Furthermore, in step 1), the reaction solvent is any one of chloroform, dichloromethane and toluene.
[0024] Furthermore, in step 1), the reaction temperature of the acyl chlorination reaction is 30-60°C.
[0025] Furthermore, in step 1), the reaction time of the acyl chlorination reaction is 3 to 6 hours.
[0026] Furthermore, in step 2), the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride, 2,4-dihydroxybenzophenone and catalyst 2 represented by formula (2) is 1 to 1.1:1 to 1.2:1.
[0027] Furthermore, in step 2), catalyst 2 is any one of triethylamine, ferrous chloride and aluminum chloride.
[0028] Furthermore, in step 2), the reaction solvent is any one of chloroform, dichloromethane and toluene.
[0029] Furthermore, in step 2), the reaction temperature of the esterification reaction is 20-40°C.
[0030] Furthermore, in step 2), the reaction time of the esterification reaction is 8 to 12 hours.
[0031] Due to the adoption of the above technology, the present invention has the following beneficial effects compared with the prior art:
[0032] (1) The migration-resistant composite anti-aging agent prepared by the present invention has a simple preparation process, mild conditions, low production cost, moderate molecular weight, reasonable structure, and is not easy to migrate and move out of the material surface.
[0033] (2) The migration-resistant composite anti-aging agent prepared by the present invention has good compatibility with the polymer matrix material. The elongation at break of the high-density polyethylene pipe added with 0.5 wt % of the anti-aging agent is greatly increased, and the toughness is significantly improved.
[0034] (3) The migration-resistant composite antioxidant prepared by the present invention has significant structural advantages. The hydroxyl group at the 4-position of 2,4-dihydroxybenzophenone is replaced by an -OCOR group, which is an electron-donating group. This increases the electron cloud density on the benzene ring and can shift the wavelength of the main ultraviolet absorption peak from the original 260 nm to 300-400 nm in the long-wave direction. At the same time, the ultraviolet absorption capacity is enhanced. Furthermore, the connection with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid enhances the compatibility with the polymer matrix and improves the stability.
[0035] (4) The migration-resistant composite antioxidant prepared by the present invention has the functions of both hindered phenol compounds capturing active free radicals and benzophenone compounds absorbing ultraviolet light. From the analysis of the material aging mechanism, the benzophenone structure solves the harm of light aging degradation from the source, while the hindered phenol compounds can prevent the further chain scission degradation of the broken molecular chains. Therefore, the anti-aging performance of the composite antioxidant is significantly improved, and the scope of application is also wider. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the infrared spectrum of the target product prepared in Example 1.
[0037] Figure 2 A line graph of the change in tensile strength of the blank sample, comparative examples 1-3 and Example 1 was prepared before and after aging.
[0038] Figure 3 The line graph of the elongation at break of the blank sample, comparative examples 1-3 and example 1 before and after aging is shown.
[0039] Figure 4 A line graph of the variation in bending strength of the blank sample, comparative examples 1-3 and example 1 was prepared before and after aging.
[0040] Figure 5 A line graph of the impact strength change of the blank sample, comparative examples 1-3 and example 1 was prepared before and after aging. DETAILED DESCRIPTION
[0041] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0042] The raw materials used in the following examples of the present invention are described as follows:
[0043] 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, 2,4-dihydroxybenzophenone, catalyst and solvent raw materials are all commercially available conventional products.
[0044] The determination methods of chemical extraction resistance, tensile strength, flexural strength, impact strength and plastic aging test involved in the following embodiments of the present invention are specifically introduced as follows:
[0045] The test method for chemical extraction resistance shall comply with the relevant provisions of ASTM D1239, the test method for tensile strength shall comply with the relevant provisions of GB / T 1040.2-2006, the test method for flexural strength shall comply with the relevant provisions of GB / T9341-2008, the test method for impact strength shall comply with the relevant provisions of ISO 179-1:2000, and the test method for plastic aging test shall comply with the relevant provisions of GB / T16422.2.
[0046] Example 1
[0047] A preparation method and application of a migration-resistant composite anti-aging agent, comprising the following steps:
[0048] (1) Weigh 5.56 g of 3,5-di-tert-butyl-4-hydroxybenzene propionic acid and dissolve it in a 250 ml three-necked flask filled with 50 ml of chloroform. Take 4 ml of thionyl chloride and slowly add it to the solution. Heat it to 50° C. under a nitrogen atmosphere, drop 0.075 g of N,N-dimethylformamide, and let it stand for 5 hours under condensation and reflux conditions, and then treat the tail gas. After the reaction is completed, distill under reduced pressure to remove the solvent and unreacted thionyl chloride to obtain the reaction intermediate 3,5-di-tert-butyl-4-hydroxybenzene propionyl chloride.
[0049] (2) Weigh 3 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride and dissolve it in 20 ml of chloroform. Separately, take 2 g of 2,4-dihydroxybenzophenone and dissolve it in 30 ml of chloroform. In an ice bath (0-5° C.), slowly drop the solution containing 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride into the solution containing 2,4-dihydroxybenzophenone. After the dropwise addition, let it stand for 10 minutes. Then, add 1.01 g of triethylamine and let it stand for 10 minutes. The reaction mixture is placed at 30° C. to react for 12 hours. After the esterification reaction is completed, the chloroform solvent is removed by rotary evaporation and dried to obtain a viscous dark brown final product, which is a migration-resistant composite anti-aging agent.
[0050] The target product prepared in this example was detected by infrared spectrometer. Figure 1 The infrared spectrum shown shows that at 3628 cm -1 and 1216cm -1 Two groups of absorption peaks appeared at the phenolic hydroxyl group, which are the symmetrical stretching vibration of OH and the bending vibration of CO.
[0051] At 2960cm -1 and 2870cm -1The absorption peak at indicates the existence of symmetric stretching vibration and asymmetric stretching vibration of methyl group.
[0052] At 1706cm -1 The absorption peak at indicates the existence of stretching vibration of the ester group.
[0053] At 1626cm -1 The absorption peak at indicates the presence of asymmetric vibration of the carbonyl group.
[0054] Therefore, it can be proved that the product molecule has the following structural formula:
[0055]
[0056] (3) 100 parts by weight of HDPE 5000S resin and 0.5 parts by weight of migration-resistant composite anti-aging agent were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes to make them uniform, and then pulverized and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0057] Example 2
[0058] A preparation method and application of a migration-resistant composite anti-aging agent, comprising the following steps:
[0059] (1) Weigh 6 g of 3,5-di-tert-butyl-4-hydroxybenzene propionic acid and dissolve it in a 250 ml three-necked flask filled with 50 ml of toluene. Take 4 ml of thionyl chloride and slowly add it to the solution. Heat it to 60° C. under a nitrogen atmosphere, drop 0.08 g of N,N-dimethylformamide, and let it stand for 3 hours under condensation and reflux conditions, and then treat the tail gas. After the reaction is completed, distill under reduced pressure to remove the solvent and unreacted thionyl chloride to obtain the reaction intermediate 3,5-di-tert-butyl-4-hydroxybenzene propionyl chloride.
[0060] (2) Weigh 2.97 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride and dissolve it in 40 ml of toluene. Separately, take 2.14 g of 2,4-dihydroxybenzophenone and dissolve it in 30 ml of toluene. In an ice bath (0-5° C.), slowly drop the solution containing 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride into the solution containing 2,4-dihydroxybenzophenone. After the dropwise addition, let it stand for 10 minutes. Then slowly add 1.2 g of ferrous chloride and let it stand for 10 minutes. The reaction mixture is placed at 40° C. to react for 8 hours. After the esterification reaction is completed, filter out the ferrous chloride, remove the toluene solvent by rotary evaporation, and dry to obtain a viscous dark brown final product, a migration-resistant composite antioxidant.
[0061] (3) 100 parts by weight of HDPE 5000S resin and 0.5 parts by weight of migration-resistant composite anti-aging agent were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes to make them uniform, and then pulverized and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0062] Example 3
[0063] A preparation method and application of a migration-resistant composite anti-aging agent, comprising the following steps:
[0064] (1) Weigh 5.56 g of 3,5-di-tert-butyl-4-hydroxybenzene propionic acid and dissolve it in a 250 ml three-necked flask filled with 100 ml of dichloromethane. Take 4 ml of thionyl chloride and slowly add it to the solution. Heat it to 30° C. under a nitrogen atmosphere, drop 0.1 g of triethylamine, and let it stand for 6 hours under condensation reflux conditions. Then, treat the tail gas. After the reaction is completed, distill under reduced pressure to remove the solvent and unreacted thionyl chloride to obtain the reaction intermediate 3,5-di-tert-butyl-4-hydroxybenzene propionyl chloride.
[0065] (2) Weigh 3 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride and dissolve it in 20 ml of dichloromethane. Separately, take 2 g of 2,4-dihydroxybenzophenone and dissolve it in 30 ml of dichloromethane. In an ice bath (0-5° C.), slowly drop the solution containing 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride into the solution containing 2,4-dihydroxybenzophenone. After the dropwise addition, let it stand for 10 minutes. Then, add 1.3 g of aluminum chloride and let it stand for 10 minutes. The reaction mixture is placed at 20° C. to react for 12 hours. After the esterification reaction is completed, the dichloromethane solvent is removed by rotary evaporation and dried to obtain a viscous dark brown final product, a migration-resistant composite anti-aging agent.
[0066] (3) 100 parts by weight of HDPE 5000S resin and 0.5 parts by weight of migration-resistant composite anti-aging agent were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes to make them uniform, and then pulverized and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0067] Comparative Example 1
[0068] 100 parts by weight of HDPE 5000S resin and 0.5 parts by weight of 3,5-di-tert-butyl-4-hydroxybenzenepropionic acid were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes, and then crushed and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0069] Comparative Example 2
[0070] 100 parts by weight of HDPE 5000S resin and 0.5 parts by weight of 2,4-dihydroxybenzophenone were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes, and then crushed and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0071] Comparative Example 3
[0072] 100 parts by weight of HDPE 5000S resin, 0.25 parts by weight of 2,4-dihydroxybenzophenone and 0.25 parts by weight of 3,5-di-tert-butyl-4-hydroxybenzenepropionic acid were put into a torque rheometer, mixed at 200°C and 90 r / min for 8 minutes to make them uniform, and then crushed and dried in a 60°C oven overnight to obtain an aging-resistant high-density polyethylene material.
[0073] The quality test results of the high-density polyethylene films prepared in Comparative Examples 1-3 and Example 1 after extraction at different times were statistically compiled, and the results are shown in Table 1.
[0074] Table 1 Quality of films of Comparative Examples 1-3 and Example 1 after extraction at different times
[0075]
[0076] It can be seen from the data in Table 1 that with the extension of the extraction time, after 120h of solvent extraction, the mass of the aging-resistant polyethylene film prepared in Comparative Example 1 decreased from 0.3062g to 0.3056g, the overall mass loss rate was 0.20%, and the antioxidant migration rate was 39.19%; the mass of the aging-resistant polyethylene film prepared in Comparative Example 2 decreased from 0.3348g to 0.3340g, the overall mass loss rate was 0.24%, and the antioxidant migration rate was 47.79%; the mass of the aging-resistant polyethylene film prepared in Comparative Example 3 decreased from 0.3062g to 0.3056g, the overall mass loss rate was 0.20%, and the antioxidant migration rate was 39.19%; .3468g dropped to 0.3461g, the overall mass loss rate was 0.20%, and the additive migration rate was 40.10%; the mass of the aging-resistant polyethylene film prepared in Example 1 dropped from 0.3040g to 0.3036g, the mass loss rate was 0.13%, the antioxidant migration rate was 26.32%, and the migration resistance of the antioxidant was significantly improved. This is because the chemical combination of the two small molecule additives increases the molecular weight of the antioxidant and further enhances the stability of the antioxidant and its compatibility with the polymer matrix.
[0077] The mechanical properties of polymer materials can directly reflect the aging resistance of the materials. By testing the tensile strength, elongation at break, bending strength and impact strength of the materials, the higher the retention rate of each mechanical property after aging, the better the anti-aging performance of the anti-aging agent. High-density polyethylene without adding antioxidant and adding the migration-resistant composite anti-aging agent prepared by the present invention are made into standard specimens required for various mechanical property tests, and mechanical property tests are carried out to evaluate the anti-aging performance of the migration-resistant composite anti-aging agent prepared by the present invention.
[0078] Plastic aging test: Place the prepared sample into a UV accelerated aging test chamber, irradiance (340nm): 0.5w / m 2 , relative humidity: 60%, blackboard temperature: 65℃, rainfall cycle: 18min / 102min (water spraying time / no water spraying time), aging test was carried out, 100h as a cycle, and 3 cycles were done in total. After xenon lamp aging, the impact, tensile and bending properties were measured using an impact testing machine and a universal material testing machine.
[0079] Table 2 Mechanical properties of high-density polyethylene pipe products prepared from pure materials, comparative examples 1-3 and example 1 after different aging times
[0080]
[0081]
[0082] The decline in mechanical properties indicates that the molecular chain is broken and the material is aged. In the UV accelerated aging test chamber, under the combined effects of UV radiation, high temperature and rain simulation, the migration resistance and stability of the antioxidant in the polymer matrix are particularly important. Poor antioxidants or UV absorbers will slowly migrate out of the material surface due to the effects of temperature and rain and lose their original performance as the aging time increases. It can be seen from the data in Table 2 that the material becomes brittle as a whole after aging, and the tensile strength and flexural strength are slightly improved. When the aging time is 300h, the elongation at break of the specimen without the addition of antioxidant dropped from 383.97% to 5.27%, the retention rate was 1.37%, and the impact strength was reduced from 105.65KJ / M 2 Reduced to 6.25KJ / M 2 , the retention rate is 5.92%, and there is no antioxidant effect; the elongation at break of the aging-resistant high-density polyethylene strip prepared in comparative example 1 was reduced from 458.92% to 25.70%, the retention rate was 5.60%, and the impact strength was reduced from 110.68KJ / M 2 Reduced to 29.35KJ / M 2, retention rate 26.52%, long-term anti-aging effect is poor; the elongation at break of the aging-resistant high-density polyethylene strip prepared in comparative example 2 was reduced from 574.10% to 174.23%, the retention rate was 30.35%, and the impact strength was reduced from 107.07KJ / M 2 Reduced to 70.68KJ / M 2 , retention rate 66.01%, long-term anti-aging effect is general; the elongation at break of the aging-resistant high-density polyethylene strip prepared in comparative example 3 was reduced from 456.03% to 69.72%, the retention rate was 15.29%, and the impact strength was reduced from 108.35KJ / M 2 Reduced to 62.77KJ / M 2 , retention rate of 57.93%, long-term anti-aging effect is general; the elongation at break of the aging-resistant high-density polyethylene strip prepared in Example 1 was reduced from 720.52% to 355.42%, the retention rate was 49.33%, and the impact strength was reduced from 105.94KJ / M 2 Reduced to 97.45KJ / M 2 , the retention rate is 91.99%, and the long-term anti-aging effect is excellent. This is because the chemical combination increases the molecular weight of the anti-aging agent, further enhancing the stability and migration resistance of the anti-aging agent. At the same time, the anti-aging agent has excellent compatibility with the polymer matrix. After adding it, the elongation at break of the polymer resin is greatly increased, so that it can achieve efficient and lasting anti-aging effect. In addition, the change in the structure of 2,4-dihydroxybenzophenone increases the electron cloud density on the benzene ring, so that the main ultraviolet absorption peak wavelength moves from the original 260nm to the long-wave direction to 300-400nm, enhancing the ultraviolet absorption ability.
[0083] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The protection scope of the present invention should be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims, that is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A migration-resistant composite antioxidant, characterized in that: It has the structure shown in formula (1): Formula (1).
2. The method for preparing the migration-resistant composite anti-aging agent according to claim 1, characterized in that: The steps include: 1) In the presence of catalyst 1, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid is reacted with thionyl chloride to obtain a 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid chloride intermediate; 2) In the presence of catalyst 2, 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride and 2,4-dihydroxybenzophenone are subjected to an esterification reaction to obtain the migration-resistant composite antioxidant.
3. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 1), the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to thionyl chloride is 1 to 1.2:
1.
4. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 1), catalyst 1 is any one of N,N-dimethylformamide, 4-dimethylaminopyridine and triethylamine.
5. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 1), the reaction temperature of the acyl chloride reaction is 30 to 60° C. and the reaction time is 3 to 6 hours.
6. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 2), the molar ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride, 2,4-dihydroxybenzophenone and catalyst 2 is 1-1.1:1-1.2:
1.
7. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 2), catalyst 2 is any one of triethylamine, ferrous chloride and aluminum chloride.
8. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 2), the reaction temperature of the esterification reaction is 20 to 40° C. and the reaction time is 8 to 12 hours.
9. The method for preparing the migration-resistant composite anti-aging agent according to claim 2, characterized in that: In step 1), the reaction solvent is any one of chloroform, dichloromethane and toluene; in step 2), the reaction solvent is any one of chloroform, dichloromethane and toluene.
10. Use of the migration-resistant composite anti-aging agent according to claim 1 in the preparation of anti-aging polymer materials, characterized in that: The polymer material includes a high-density polyethylene pipe, the density of which is 0.941 to 0.960 g / cm³ and the melt flow rate of which is 2.20 to 2.26 g / 10 min.
Citation Information
Patent Citations
Synergistic UV stabilizer-compsns. for plastics - esp. polyolefins
CH597290A5
Preparation method of polyamino silane coupling agent modified antioxidant and silicon dioxide loaded
CN115197588A
Oxidation-resistant and yellowing-resistant composite board
CN118374090A
UV stabilisers for plastics, esp. polyolefins - contg. phenols, amides and nickel cpds.
DE2502016A1
Process for stabilizing magenta couplers and the corresponding image dyes in photographic materials
US5145766A